Project Management Suitable for the Digital World - Bedi, Hitesh (Digital Repository of Theses - SSBM Geneva, 2024)
This study attempts to make sincere efforts to analyze the challenges and barriers that global project managers are facing in a rapidly changing business environment. This proposal attempts to decode the unique challenges to global project management and the magnitude of their effect on project team performance in the global business environment. The present study aims to contribute some impactful findings in the existing literature and try to extract practical implications with a focus on the potential opportunities and barriers and their remedies for multinational organizations. With the need to adapt to the rapidly changing environment and the digital shift, it is necessary to spend efforts to research how the new technologies require traditional project managers to adapt to support the digital transformation. The primary objective of this research is to investigate how digitalization has impacted the demands placed on project management. By doing so, it aims to shed light on the disparities between the skill sets of traditional project managers and the proficiencies necessary for successfully navigating digital transformation. With this in mind, the study endeavours to pinpoint the most suitable project management methodologies and tools that project managers can utilize to capitalize on the advantages of digital transformation.